Zinc-iodine battery based on zinc bromide electrolyte

By adopting the TBBQ and Br- dual catalytic system in zinc-iodine batteries, the problem of slow reaction kinetics and many side reactions in zinc-iodine batteries is solved, and a zinc-iodine battery with high magnification, large capacity and stability is achieved.

CN119601673AActive Publication Date: 2025-03-11WEIFANG UNIV OF SCI & TECH

Patent Information

Application Number
CN202510143763.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-11
Estimated Expiration
2045-02-10

AI Technical Summary

Technical Problem

The two-step reaction kinetics of zinc-iodine batteries are slow, have many side reactions, have poor reversibility of the reaction, and are prone to shuttle effects on charging products, resulting in poor performance, including low Coulomb efficiency, low capacity, and poor circulation performance.

Method used

Using a dual catalytic system of TBBQ and Br-, the redox reaction of TBBQ and Br- at the same potential is provided, and the IBr and Br2 generated in the charging state are captured by bromine elements, inhibiting their shuttle, thereby accelerating the reaction kinetics of zinc-iodine batteries.

Benefits of technology

The construction of high-magnification and large-capacity zinc-iodine batteries has been achieved, which improves the reaction kinetics and energy storage capacity of zinc-iodine batteries, and enhances the stability of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601673A_ABST
    Figure CN119601673A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc-iodine battery based on a zinc bromide electrolyte, and belongs to the technical field of chemical energy batteries. The zinc-iodine battery comprises a positive electrode, a negative electrode and an electrolyte, the positive electrode is a positive electrode containing a dual catalytic system, and the electrolyte is an electrolyte containing zinc bromide; the positive electrode containing the dual catalytic system comprises a dual catalytic system material, conductive carbon and a binder; the dual catalytic system material is obtained by mixing an iodine elementary substance and a non-polar compound which contains halogen and a carbon group and has a symmetrical structure. The preparation method comprises the following steps: adding tetrabromo-p-benzoquinone and elemental iodine into an organic solvent for dissolving, and removing the organic solvent to obtain the dual catalytic system material, wherein the non-polar compound containing halogen and a carbon group and having a symmetrical structure is tetrabromo-p-benzoquinone. The two-step reaction of the zinc-iodine battery is doubly catalyzed by the TBBQ and the Br <->, the reaction kinetics is improved, and meanwhile, the TBBQ and the Br <-> can be subjected to oxidation-reduction reaction at the same potential to provide extra capacity, so that the construction of the high-rate and high-capacity zinc-iodine battery is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical energy batteries, and in particular to a zinc-iodine battery based on zinc bromide electrolyte. Background Art

[0002] Aqueous zinc-based batteries have excellent safety, low cost, sustainability, low electrode potential (-0.76 Vvs. SHE) and high specific capacity (820 mAh g -1 ) and other advantages, and has great application potential. At present, the positive electrode of aqueous zinc-based batteries mainly includes crystalline materials such as manganese dioxide and vanadium oxide. The reaction process of these materials is the repeated intercalation and extraction of zinc ions, which often leads to the structural collapse and dissolution of the positive electrode material, resulting in small capacity and poor cycle stability. Transferring the stored charge to conversion chemistry by utilizing the redox reaction of halogens (such as I, Br and Cl) is a method that can avoid the structural collapse of the positive electrode material. Halogens have rich valence states, allow a large amount of charge transfer, and are abundant in nature. Among them, iodine is an ideal choice. Iodine is solid at ambient temperature and has a good redox potential in aqueous electrolytes. It has been deeply studied in metal-based iodine batteries such as Li-I2, Ni-I2, Mg-I2, Al-I2, and Zn-I2. Many studies have focused on mitigating the iodine shuttle effect through methods such as physical adsorption, chemical confinement, and the development of new electrolytes to improve the performance of iodine redox electrodes and promote their practical applications.

[0003] Conventional iodine electrodes are usually used at a lower voltage (0.54 V vs. SHE) and only involve I / I − The theoretical specific capacity of the one-step redox transfer is only 211 mAh g -1 , which also limits the energy density. Recently, researchers have developed electrolytes that can achieve both I / I - and I + / I Two-step reaction zinc-iodine battery, increasing capacity to 422 mAh g -1 , the working voltage increased to 1.02 V vs. SHE. However, the development of two-step reaction zinc-iodine batteries is still in its early stages and still faces many problems. For example, the two-step reaction kinetics of zinc-iodine batteries are relatively slow, there are many side reactions, the reversibility of the reaction is poor, and the charging products are prone to shuttle effects. These problems will lead to poor performance of zinc-iodine batteries, including: low coulombic efficiency, low capacity, poor cycle performance, etc. In view of the shortcomings of the two-step reaction in zinc-iodine batteries, if a dual catalytic system can be designed based on the principle of redox catalysis at similar potentials, the reaction kinetics of zinc-iodine batteries can be accelerated, and additional capacity can be provided when redox reactions occur at the same potential, thereby realizing the construction of high-rate and large-capacity zinc-iodine batteries. Summary of the invention

[0004] In view of the above prior art, the purpose of the present invention is to provide a zinc-iodine battery based on zinc bromide electrolyte. - Dual catalysis of the two-step reaction of zinc-iodine battery improves the reaction kinetics, while TBBQ and Br - It will also undergo redox reactions at the same potential to provide additional capacity, thereby enabling the construction of high-rate, large-capacity zinc-iodine batteries.

[0005] To achieve the above object, the present invention adopts the following technical solution: In a first aspect of the present invention, a zinc-iodine battery based on a zinc bromide electrolyte is provided, wherein the zinc-iodine battery is a two-step reaction zinc-iodine battery, and the zinc-iodine battery comprises a positive electrode, a negative electrode and an electrolyte; the positive electrode is a positive electrode containing a dual catalytic system, and the electrolyte is an electrolyte containing zinc bromide; The positive electrode containing the dual catalytic system comprises a dual catalytic system material, conductive carbon and a binder; The dual catalytic system material is obtained by mixing iodine element and a non-polar compound with a symmetrical structure containing halogen and carbon base; the halogen is bromine.

[0006] Preferably, the non-polar compound containing halogen and carbon group and having a symmetrical structure is tetrabromo-p-benzoquinone.

[0007] Preferably, the dual catalytic system material is prepared by the following method: Tetrabromobenzoquinone and iodine are added to an organic solvent to dissolve, and then the organic solvent is removed to obtain TBBQ@I2 material, which is a dual catalytic system material.

[0008] Preferably, the mass ratio of tetrabromo-p-benzoquinone to elemental iodine is 3:1 to 1:3.

[0009] Preferably, the organic solvent is selected from ether, acetone, petroleum ether, chloroform, carbon tetrachloride, benzene or toluene.

[0010] Preferably, the amount of the dual catalytic system material added to the positive electrode is 0.5-1.5 mg / cm 2 .

[0011] Preferably, the preparation method of the positive electrode is: The dual catalytic system material, conductive carbon and a binder are mixed and then ground and coated to obtain a positive electrode.

[0012] Preferably, the negative electrode is zinc foil.

[0013] Preferably, the electrolyte is a single zinc bromide solution or a zinc bromide mixed solution; the zinc bromide mixed solution contains zinc bromide and zinc sulfate, zinc bromide and zinc perchlorate, or zinc bromide and zinc trifluoromethanesulfonate.

[0014] Preferably, the concentration of the electrolyte is 0.2~3M.

[0015] The second aspect of the present invention provides the use of the above zinc-iodine battery in improving the reaction kinetics of a two-step reaction and improving the energy storage capacity.

[0016] Beneficial effects of the present invention: (1) The present invention aims at the two-step reaction of zinc-iodine battery, establishes redox catalysis with the same potential respectively, and designs a dual catalytic system to solve the problem of slow reaction kinetics of zinc-iodine battery. The design idea is unique and the design theory is innovative.

[0017] (2) The present invention uses TBBQ and Br - It will also provide additional capacity for the redox reaction at the same potential in the two-step reaction of the zinc-iodine battery, realize a multi-electron professional reaction system, increase the capacity of the material, and facilitate the preparation of high-energy density batteries.

[0018] (3) The bromine element on TBBQ used in the present invention can also capture IBr and Br2 generated during charging, inhibit their shuttling, and improve the stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a Fourier transform infrared spectrum of iodine in Comparative Example 1 of the present invention; Figure 2 The scanning and elemental analysis diagrams of iodine in Comparative Example 1 of the present invention, wherein (a) to (c) are scanning electron microscope images of the sample at different magnifications; (d) is a mapping diagram of the C element; (e) is a mapping diagram of the O element; (f) is a mapping diagram of the I element; Figure 3 Cyclic voltammetry test of I2@C at a scan rate of 2 mV / s in Comparative Example 1 of the present invention; Figure 4 The I2@C in Comparative Example 1 of the present invention is 2A g -1 Long cycle curve under current density; Figure 5 This is the Fourier infrared spectrum of TBBQ@I2 in Comparative Example 2 of the present invention; Figure 6The scanning and elemental analysis diagrams of TBBQ@I2 in Comparative Example 2 of the present invention, wherein (a) to (c) are scanning electron microscope images of the sample at different magnifications; (d) is a mapping diagram of the C element; (e) is a mapping diagram of the O element; (f) is a mapping diagram of the I element; (g) is a mapping diagram of the Br element; Figure 7 The cyclic voltammetry test of TBBQ@I2 in comparative example 2 of the present invention at a scanning rate of 2 mV / s; Figure 8 Cyclic voltammetry test of TBBQ and TBB at a scan rate of 2 mV / s in Comparative Example 2 of the present invention; Fig. 9 The TBBQ@I2 in Comparative Example 2 of the present invention is 2A g -1 Long cycle curve under current density; Fig.10 The cyclic voltammetry test of I2@C at a scan rate of 2 mV / s in Comparative Example 3 of the present invention; Fig.11 The I2@C in Comparative Example 3 of the present invention is 2A g -1 Long cycle curve under current density; Fig.12 Cyclic voltammetry test of TBBQ@I2 at a scan rate of 2 mV / s in an embodiment of the present invention; Fig.13 The TBBQ@I2 in the embodiment of the present invention is 2A g -1 Long cycle curves at different current densities. DETAILED DESCRIPTION

[0020] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0021] As introduced in the background technology section, the two-step reaction kinetics of zinc-iodine batteries are relatively slow, there are many side reactions, the reversibility of the reaction is poor, and the charging products are prone to shuttle effects.

[0022] Based on this, the purpose of the present invention is to provide a zinc-iodine battery based on zinc bromide electrolyte. According to the principle of similar potential redox catalysis, the present invention designs a dual catalytic system: first, the redox potential of the carbonyl group on tetrabromobenzoquinone (TBBQ) is similar to that of 2I - - 2e - The potential of the I2 reaction (0.54 V vs. SHE) is close, which can accelerate the first step 2I of the zinc-iodine battery - - 2e- I2 reaction kinetics, in addition, TBBQ can provide additional capacity; secondly, in zinc bromide electrolyte, I2- 2e - + 2Br - The potential of 2 IBr (1.02 V vs. SHE) and 2Br - - 2e - The potential of Br2 (1.09 V vs. SHE) is very close. The use of zinc bromide electrolyte can not only accelerate the second step of zinc iodine battery I2- 2e - + 2Br - 2IBr(I2 / I + ) reaction kinetics, while Br − The redox reaction is converted into Br2 to provide additional capacity. The bromine element on TBBQ can also capture IBr and Br2 generated in the charging state, inhibit their shuttle, and improve the stability of the battery. - As a catalyst, a dual catalytic system for the two-step electrode reaction in the zinc-iodine battery is realized, which accelerates the reaction kinetics of the zinc-iodine battery. - It will also undergo redox reactions at the same potential to provide additional capacity, thereby enabling the construction of high-rate, large-capacity zinc-iodine batteries.

[0023] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0024] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.

[0025] Example: Zinc-iodine battery containing a dual catalytic system of tetrabromobenzoquinone (TBBQ) and zinc bromide S1: Dissolve 0.5 g of iodine (I2) and 1 g of TBBQ in 100 mL of chloroform solvent, and then evaporate the chloroform using a rotary evaporator to obtain TBBQ@I2 material.

[0026] S2: The prepared TBBQ@I2 material (60 mg), conductive carbon acetylene black (30 mg) and binder carboxymethyl cellulose (CMC) (10 mg) were ground and smeared onto a titanium foil (50 μm) current collector. The TBBQ@I2 material loading was 1.0 mg / cm 2The aqueous zinc-iodine battery was assembled using zinc foil as the negative electrode, glass fiber as the separator, 3M zinc trifluoromethanesulfonate + 0.3M zinc bromide mixed solution as the electrolyte, and a Swagelok battery mold.

[0027] The assembled Swagelok battery aqueous zinc-iodine battery was tested using Chenhua CHI660E and Blue Power CT2001A electrochemical workstations. The kinetic reversibility of its redox reaction was observed at a scan rate of 2 mV / s, and its charge and discharge curves were tested at a current density of 2 A / g to determine its capacity.

[0028] Fig.12 Indicates that the TBBQ@I2 material prepared in Example S1 is - Under the action of 2 mV / s scanning speed, the cyclic voltammetry curve shows that in the voltage range of 0.6 V-2.0 V, the peak voltages of oxidation peaks are about 1.2 V, 1.55 V, and 1.75 V, and the peak voltages of reduction peaks are about 1.06 V, 1.4 V, and 1.6 V. The redox peak at a voltage of 1.2 V is the first step of the zinc-iodine battery reaction (I2 / I - ), and the peak voltage of the reduction peak at 1.6 V increases. TBBQ participates in the reaction and provides additional capacity. The redox peak at 1.2 V is the second step reaction of the zinc-iodine battery (I2 / I + ) in Br - Under the action of , the reaction can be reversed and improved, thus inhibiting the side effects. Fig.13 The TBBQ@I2 positive electrode in the zinc-iodine battery prepared in the representative example is in Br - Under the action of -1 Under the 100-cycle long cycle curve, the battery discharge capacity is basically maintained at 380 mAh g -1 The battery capacity and cycle are greatly improved, which is mainly due to the TBBQ and Br in the embodiment - A dual catalytic system was formed.

[0029] Comparative Example 1: Zinc-iodine battery without tetrabromobenzoquinone (TBBQ) and zinc bromide system S1: Dissolve 0.5 g of iodine (I2) in 100 mL of chloroform solvent, and then evaporate the chloroform using a rotary evaporator to obtain I2 material.

[0030] S2: The prepared I2 material (60 mg), conductive carbon acetylene black (30 mg) and binder carboxymethyl cellulose CMC (10 mg) were ground and smeared onto a titanium foil (50 μm) current collector. The I2 material loading was 1.0 mg / cm 2The aqueous zinc-iodine battery was assembled using zinc foil as the negative electrode, glass fiber as the separator, 3M zinc trifluoromethanesulfonate solution as the electrolyte, and a Swagelok battery mold.

[0031] S3: The assembled Swagelok battery aqueous zinc-iodine battery was tested using Chenhua CHI660E and Blue Power CT2001A electrochemical workstations. The kinetic reversibility of its redox reaction was observed at a scan rate of 2 mV / s, and its charge and discharge curves were tested at a current density of 2A / g to determine its capacity.

[0032] Figure 1 The infrared curve of the I2 material prepared by S1 in Comparative Example 1, 400-800 cm -1 The series of peaks here represent the stretching vibration peaks of iodine molecules. Figure 2 The SEM and mapping images of the I2 positive electrode material in Comparative Example 1 show that the C element, I element, and O element are evenly distributed on the surface of the electrode sheet, proving that the electrode sheet was successfully prepared. Figure 3 The cyclic voltammetry curve of I2 in the zinc-iodine battery prepared in Comparative Example 1 at a scanning rate of 2 mV / s shows that within the voltage range of 0.5 V-2.0 V, there is a pair of obvious redox peaks at the positive electrode of I2, which are the first step reaction of the zinc-iodine battery (I2 / I - However, an asymmetric peak still appeared at 2.0 V, proving that the second step reaction of the zinc-iodine battery (I2 / I + ), side reactions are prone to occur and the kinetics are slow. Figure 4 The positive electrode I2 in Comparative Example 1 is at a current density of 2 A g -1 The 100-cycle long cycle curve shows that the battery discharge capacity increases from 78 mAh g to -1 Down to 59mAh g -1 The battery capacity and cycle performance are poor, which is mainly due to the fact that only the first step I2 and I - The reaction between the second step and the side effects are serious. + It cannot exist stably and the two-step reaction kinetics are slow.

[0033] Comparative Example 2: Zinc-iodine battery with tetrabromobenzoquinone (TBBQ) and without zinc bromide system S1: Dissolve 0.5 g of iodine (I2) and 1 g of TBBQ in 100 mL of chloroform solvent, and then evaporate the chloroform using a rotary evaporator to obtain TBBQ@I2 material.

[0034] S2: The prepared TBBQ@I2 material (60 mg), conductive carbon acetylene black (30 mg) and binder carboxymethyl cellulose (CMC) (10 mg) were ground and smeared onto a titanium foil (50 μm) current collector. The TBBQ@I2 material loading amount was 1.0 mg / cm 2 The aqueous zinc-iodine battery was assembled using zinc foil as the negative electrode, glass fiber as the separator, 3M zinc trifluoromethanesulfonate solution as the electrolyte, and a Swagelok battery mold.

[0035] S3: The assembled Swagelok battery aqueous zinc-iodine battery was tested using Chenhua CHI660E and Blue Power CT2001A electrochemical workstations. The kinetic reversibility of its redox reaction was observed at a scan rate of 2 mV / s, and its charge and discharge curves were tested at a current density of 2 A / g to determine its capacity.

[0036] Figure 5 The infrared curve of TBBQ@I2 prepared by S1 in Comparative Example 2, 1650-1750 cm -1 The peak at 1450-1600 cm represents the carbonyl (C=O) stretching vibration peak. -1 The series of peaks at 1600-1800 cm -1 The C=C stretching vibration peak appears at 1000 cm -1 The left and right series of peaks represent the CH bond bending vibration absorption peaks on the benzene ring, 650-900cm -1 The series of peaks at represent the stretching vibration peaks of C-Br bonds. Figure 6 The SEM and mapping images of the TBBQ@I2 material electrode sheet in Comparative Example 2 show that the C element, I element, O element, and Br element are evenly distributed on the surface of the electrode sheet, proving that TBBQ@I2 is successfully prepared. Figure 7 The cyclic voltammetry curve of TBBQ@I2 in the zinc-iodine battery prepared in comparative example 2 at a scanning rate of 2 mV / s shows that within the voltage range of 0.6V-2.0V, there are obvious redox peaks at the positive electrode of I2, with an oxidation peak voltage of about 1.25 V and a reduction peak voltage of about 1.0 V, and a voltage difference of 250mV. This pair of redox peaks is the first step reaction of the zinc-iodine battery (I2 / I - ), and the high potential side reaction was significantly suppressed, mainly because TBBQ participated in the reaction, which was beneficial to stabilize the oxygen evolution reaction. However, the peak at high potential was not obvious. This is because the second step reaction of zinc-iodine battery (I2 / I + ) in the reaction, the kinetics are slow. To further demonstrate the effect of TBBQ, the CV curves of tetrabromobenzene (TBB) and TBBQ were compared, as shown in Figure 2. Figure 8The CV curve of TBB shown in the figure has no obvious redox peaks, indicating that it has no additional capacity contribution, while the CV curve of TBBQ has a bunch of obvious redox peaks, indicating that TBBQ can provide additional capacity, and the redox peak position of TBBQ highly overlaps with the peak position of iodine, which is conducive to the catalytic reaction at the same potential. Fig. 9 The TBBQ@I2 positive electrode prepared in Comparative Example 2 was -1 The 100-cycle long cycle curve shows that the battery discharge capacity increases from 140 mAh g to -1 Down to 125 mAh g -1 The battery capacity has improved, but the single cycle is still poor. This is mainly due to the TBBQ catalyzing the first step I2 and I - The reaction between the two steps and the additional capacity is provided. The side reaction in the second step is serious. + It cannot exist stably and the second step reaction kinetics are slow.

[0037] Comparative Example 3: Zinc-iodine battery without tetrabromobenzoquinone (TBBQ) and with zinc bromide system S1: Dissolve 0.5 g of iodine (I2) in 100 mL of chloroform solvent, and then evaporate the chloroform using a rotary evaporator to obtain I2 material.

[0038] S2: The prepared I2 material (60 mg), conductive carbon acetylene black (30 mg) and binder carboxymethyl cellulose CMC (10 mg) were ground and smeared onto a titanium foil (50 μm) current collector. The I2 material loading was 1.0 mg / cm 2 The aqueous zinc-iodine battery was assembled using zinc foil as the negative electrode, glass fiber as the separator, 3M zinc trifluoromethanesulfonate + 0.3M zinc bromide mixed solution as the electrolyte, and a Swagelok battery mold.

[0039] S3: The assembled Swagelok battery aqueous zinc-iodine battery was tested using Chenhua CHI660E and Blue Power CT2001A electrochemical workstations. The kinetic reversibility of its redox reaction was observed at a scan rate of 2 mV / s, and its charge and discharge curves were tested at a current density of 2A / g to determine its capacity.

[0040] Fig.10 The cyclic voltammetry curve of I2 in the zinc-iodine battery prepared in Comparative Example 3 at a scanning rate of 2 mV / s shows that within the voltage range of 0.6V-2.0V, there are three pairs of obvious redox peaks at the positive electrode of I2, with the oxidation peak voltages being approximately 1.25V, 1.65V and 1.8V, and the reduction peak voltages being approximately 1.05V, 1.35V and 1.6V. The redox peak at a voltage of 1.65V is the second step reaction of the zinc-iodine battery (I2 / I+ ) in Br − Under the action of , the reversibility becomes better, and the side reaction is inhibited. At the same time, a pair of new redox peaks appear, which are 2Br - - 2e - Br2 reacts, providing additional capacity. Fig.11 Representative Comparative Example 3 I2 positive electrode in Br - Under the action of current density of 2 A g -1 The 100-cycle long cycle curve shows that the battery discharge capacity is basically maintained at 160 mAh g after 100 cycles. -1 The battery capacity and cycle are improved, which is mainly due to the Br - Catalyze the second step I2 and I + The reaction between the first step and the additional capacity. Fig.10 ), which is significantly weaker than the redox peak of the first step reaction of the zinc-iodine battery in the example ( Fig.12 ), indicating that the first step reaction of comparative example 3 is kinetically slow without TBBQ catalysis. In addition, it can be seen from the long cycle that the capacity of comparative example 3 is 160 mAhg -1 In the example, the capacity of the device increased to 380 mAh g after the introduction of TBBQ catalyst. -1 , the capacity has been greatly improved.

[0041] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A zinc-iodine battery based on zinc bromide electrolyte, characterized in that: The zinc-iodine battery is a two-step reaction zinc-iodine battery, comprising a positive electrode, a negative electrode and an electrolyte; the positive electrode is a positive electrode containing a dual catalytic system, and the electrolyte is an electrolyte containing zinc bromide; The positive electrode containing the dual catalytic system comprises a dual catalytic system material, conductive carbon and a binder; The dual catalytic system material is obtained by mixing iodine element and a non-polar compound with a symmetrical structure containing halogen and carbon base; the halogen is bromine.

2. The zinc-iodine battery according to claim 1, characterized in that: The non-polar compound containing halogen and carbon group and having a symmetrical structure is tetrabromo-p-benzoquinone.

3. The zinc-iodine battery according to claim 2, characterized in that: The dual catalytic system material is prepared by the following method: Tetrabromobenzoquinone and iodine are added to an organic solvent to dissolve, and then the organic solvent is removed to obtain TBBQ@I2 material, which is a dual catalytic system material.

4. The zinc-iodine battery according to claim 3, characterized in that: The mass ratio of tetrabromo-p-benzoquinone to elemental iodine is 3:1 to 1:

3.

5. The zinc-iodine battery according to claim 3, characterized in that: The organic solvent is selected from ether, acetone, petroleum ether, chloroform, carbon tetrachloride, benzene or toluene.

6. The zinc-iodine battery according to claim 1, characterized in that: The amount of the dual catalytic system material added to the positive electrode is 0.5-1.5 mg / cm 2 .

7. The zinc-iodine battery according to claim 1, characterized in that: The electrolyte is a single zinc bromide solution or a zinc bromide mixed solution; the zinc bromide mixed solution contains zinc bromide and zinc sulfate, zinc bromide and zinc perchlorate, or zinc bromide and zinc trifluoromethanesulfonate.

8. The zinc-iodine battery according to claim 7, characterized in that: The concentration of the electrolyte is 0.2~3M.

9. Use of the zinc-iodine battery according to any one of claims 1 to 8 in improving the reaction kinetics of a two-step reaction and improving the energy storage capacity.

Citation Information

Patent Citations

  • Low-temperature zinc ion battery

    CN108574085A

  • Zinc organic battery and application thereof

    CN109994785A

  • Aqueous zinc-iodine battery based on four-electron conversion reaction and electrolyte thereof

    CN111540950A

  • Rechargeable aqueous zinc ion battery with wide temperature range and long cycle life

    CN111600081A

  • Aqueous zinc-double halogen battery based on multi-electron conversion reaction and electrolyte of aqueous zinc-double halogen battery

    CN114709494A

Cited By

  • Zinc-bromine flow battery multifunctional electrolyte and preparation method thereof

    CN121011691A